Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Statistika Siswa Kelas XI di SMKN 1 Rangkasbitung - Neni Heryani (Universitas Sultan Ageng Tirtayasa, 2022)
Based on UNESCO data, the quality of mathematics education ini Indonesia is still very low. In addition, based on the results of observations at SMKN 1 Rangkasbitung onlyh 30% of the totality number of students who achieved the KKM score, this situation of the PBL model can improve the statistical learning outcomes of class XI TKJ students at SMKN 1 Rangkasbitung. The research subject were 37 students of class XI TKJ at SMKN 1 Rangkasbitung, the object of research was to apply the PBL model. The technique of collecting data was observation and student learning outcomes through a post test which was then processed using descriptive data analysis. Based on the results of the study, it showed an increase in the value of knowledge and skills in cycle 1 and cycle 2 besides that it could improve student skills and teacher performance so that it could be said that the PBL problem learning model was feadsible to be used in learning mathematics for class XI TKJ students on statistical material at SMKN 1 Rangkasbitung.